2010
DOI: 10.1038/sc.2010.47
|View full text |Cite
|
Sign up to set email alerts
|

Corticotrophin-releasing hormone (CRH) facilitates axon outgrowth

Abstract: Objective: To evaluate the role of corticotrophin-releasing hormone (CRH) in facilitating axon outgrowth. Background: Injured neural tissue is difficult to regenerate; the mechanism has not been fully understood.Methods: A rat model of spinal cord transection injury was developed. Levels of BDNF, CRH and oligodendrocyte glycoprotein (OMgp) in injured spinal cord were monitored dynamically after surgery. Cellular interaction among rat dorsal root ganglia (DRG) cells, oligocondrocytes and microglial cells was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Moreover, a co-overexpression of CRH with pain-relevant neuropeptides has been observed in DRG and nociceptors [31]. Another hypothesis suggests a role in nerve regeneration by releasing brain-derived neurotrophic factor (BDNF) and promoting axonal outgrowth [13]. So far, neuronal CRH expression has been described mainly in the hypothalamus [32]: only little is known about its role in sensory neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a co-overexpression of CRH with pain-relevant neuropeptides has been observed in DRG and nociceptors [31]. Another hypothesis suggests a role in nerve regeneration by releasing brain-derived neurotrophic factor (BDNF) and promoting axonal outgrowth [13]. So far, neuronal CRH expression has been described mainly in the hypothalamus [32]: only little is known about its role in sensory neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an overexpression of transient potential receptor V1 (TRPV1) and voltage-gated sodium channels has been observed in spared dorsal root ganglia (DRG) neurons after ligation [12]. However, most research on “uninjured afferent” neurons [13] originate from comparisons between injured and not-injured DRG (e.g. L4 after spinal nerve ligation (SNL) of L5, or spared nerve branches after partial ligation, see [14]) rather than neighboring neurons of the same DRG.…”
Section: Introductionmentioning
confidence: 99%
“…Existing literature on CRH is limited and only indirectly applies to oligodendrogenesis [288,289], although CRH elevates cAMP levels in OPCs [290]. Existing research regarding NE is more abundant, and adrenoreceptors are found across the OL lineage.…”
Section: Non-classical Hormones: Neurohormones Neuromodulators and mentioning
confidence: 99%
“…Synapsins were proposed as the optimal candidates to modulate neurite outgrowth in the first stages of neuronal development, owing to their abilities to modulate polymerization and assembly of actin [48]. Recently, it has been demonstrated that corticotrophin-releasing hormone facilitates the outgrowth of axon in spinal neurons [49]. As reported by Sahin and colleagues [50], neuronal guanine nucleotide exchange factor plays an important role in Eph-mediated axon guidance by promoting outgrowth in the absence of ephrins and retraction in the presence of ephrins.…”
Section: Discussionmentioning
confidence: 99%